2011
DOI: 10.1007/s10059-011-1031-5
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Promoter Activity of Pre-B Cell Stage-Specific Crlz1 Gene Is Caused by One Distal LEF-1 and Multiple Proximal Ets Sites

Abstract: The promoter of pre-B cell stage-specific Crlz1 gene, whose protein translocates the cytoplasmic core binding factor β (CBFβ) into the nucleus and thereby allows its heterodimerization with Runx, has a very strong activity, which is about 25% of cytomegalovirus (CMV) promoter activity and comparable to the EF-1α promoter activity. Its transcription start site was mapped at 155 nt upstream of translation initiation codon. 5′-truncation analysis of charged amino acids rich leucine zipper 1 (Crlz1) promoter revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…3b ). LEF1 ’s role in B cell activation in B-lymphocytes has already been characterized in mouse 30 , 31 , and further, LEF1 has been strongly linked with chronic lymphocytic leukemia (CLL) 32 34 . LEF1 mediated Wnt signaling has been shown to be critical for hypothalamic neurogenesis in zebrafish 35 , 36 .…”
Section: Resultsmentioning
confidence: 99%
“…3b ). LEF1 ’s role in B cell activation in B-lymphocytes has already been characterized in mouse 30 , 31 , and further, LEF1 has been strongly linked with chronic lymphocytic leukemia (CLL) 32 34 . LEF1 mediated Wnt signaling has been shown to be critical for hypothalamic neurogenesis in zebrafish 35 , 36 .…”
Section: Resultsmentioning
confidence: 99%
“…B, Wnt3a was found to be expressed in PD36 pre-B cells among the three common (Wnt3a, Wnt5a, and Wnt10b) Wnt ligands as examined in an RT-PCR analysis. C, among three (GABP␣, Fli-1, and LEF-1) transcription factors identified to bind Crlz-1 promoter in our previous report (6), only LEF-1 was found to be expressed specifically in PD36 pre-B cells as analyzed with Western blotting. ␤-Catenin was also included in this Western blotting analysis.…”
Section: Cbf␤ a Binding Partner Of Runx Was Found To Be Localized Imentioning
confidence: 66%
“…Previously, we reported that Crlz-1 is expressed specifically in pre-B cells (4) and turned out to be a nuclear protein, thereby mobilizing cytoplasmic CBF␤ into nucleus to allow its heterodimerization with nuclear Runx and subsequent transcriptional activation of its target genes by binding to its target DNA site in a form of Runx-CBF␤-Crlz-1 ternary complex (5). In addition, the promoter of Crlz-1 gene was found to be very strong and regulated by lymphoid enhancer factor-1 (LEF-1) (6), which is a nuclear transcriptional effector of Wnt signaling pathway (7), suggesting that Crlz-1 might be a Wnt target gene.…”
mentioning
confidence: 99%
“…Charged amino acid-rich leucine zipper-1 (Crlz-1) was found to be expressed especially in the proliferating cells such as pre-B cells (19,20), spermatogonia, and Sertoli cells (21). This gene was targeted by Wnt/b-catenin signaling (20,22), and its protein was shown to function by mobilizing cytoplasmic CBFb into the nucleus to allow its heterodimerization with nuclear Runx (23). This knowledge, with many reports that canonical Wnt/b-catenin signaling is involved in the cellular proliferation (24,25), prompted us to wonder whether Crlz-1 might also be expressed in the rapidly proliferating centroblast cells within GC during humoral immune response.…”
mentioning
confidence: 99%
“…The stabilized b-catenin enters to the nucleus and binds to the promoter of the target gene with TCF/LEF for its transcriptional activation (29,30). The Crlz-1 promoter contains this TCF/LEF binding sequence motif, which was shown to bind LEF-1 together with b-catenin to activate it (20,22).…”
mentioning
confidence: 99%